2015
DOI: 10.1037/bne0000092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extinction treatments on the reduction of conditioned responding and conditioned hyperarousal in a rabbit model of posttraumatic stress disorder (PTSD).

Abstract: We have previously characterized a model of posttraumatic stress disorder (PTSD), based on classical conditioning of the rabbit nictitating membrane response (NMR), that focuses on 2 key PTSD-like features: conditioned responses to trauma-associated cues and hyperarousal. In addition to the development of conditioned NMRs (CRs) to a tone conditioned stimulus (CS) associated with a periorbital shock unconditioned stimulus (US), we have observed that rabbits also exhibit a conditioning-specific reflex modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 72 publications
2
16
1
Order By: Relevance
“…Data were analyzed from 145 rabbits that were classically conditioned using our standard NMR delay conditioning paradigm. The data came from 34 rabbits in a published study (Burhans et al, 2015) and from 111 rabbits in four unpublished studies collected over a period of several years. Subjects were male, New Zealand White rabbits ( Oryctolagus cuniculus ), supplied by Harlan (Indianapolis, IN, USA) or Charles River (Saint Constant, Quebec, Canada) weighing 2.0–2.2 kg and aged 69–77 days upon arrival.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were analyzed from 145 rabbits that were classically conditioned using our standard NMR delay conditioning paradigm. The data came from 34 rabbits in a published study (Burhans et al, 2015) and from 111 rabbits in four unpublished studies collected over a period of several years. Subjects were male, New Zealand White rabbits ( Oryctolagus cuniculus ), supplied by Harlan (Indianapolis, IN, USA) or Charles River (Saint Constant, Quebec, Canada) weighing 2.0–2.2 kg and aged 69–77 days upon arrival.…”
Section: Methodsmentioning
confidence: 99%
“…Previous CRM experiments reported NMR conditioning data averaged across all rabbits receiving paired NMR conditioning (Burhans, Smith-Bell, & Schreurs, 2015; Schreurs et al, 1995, 2000). However, averaging group NMR conditioning data is known to mask behavioral phenomena and group averages may suggest that all subjects learn at the same rate in a monotonically increasing fashion (Gallistel, Fairhurst, & Balsam, 2004; Halverson, Hoffmann, Kim, Kish, & Mauk, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, training rabbits to produce multiphasic CRs by conditioning with a tone paired with two sequential USs did not produce a multiphasic UR that paralleled the CR topography, and it was shown that CRs could be extinguished without CRM and vice versa if rabbits were given CS-alone or US-alone presentations, respectively (Schreurs et al, 2000). It was only when both treatments were combined using explicitly unpaired CS/US presentations that both CRs and CRM were extinguished simultaneously (Burhans, Smith-Bell, & Schreurs, 2015; Schreurs et al, 2000). In addition, CRs and CRM have been shown to differentially respond to systemic serotonergic, glutamatergic, and noradrenergic manipulations (Burhans, Smith-Bell, & Schreurs, 2013, 2017, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the rabbit model of PTSD, we have also shown that explicitly unpaired presentations of the CS and US effectively reduce CS responding and US hyperarousal (Buck et al, 2001, Schreurs et al, 2000). Because using the traumatic event as a means of treating PTSD is untenable, we since showed that extinguishing US hyperarousal as well as CRs using explicitly unpaired presentations of the CS and US can also be achieved when the intensity of the shock US is reduced eight-fold – an intensity that only elicits minimal responding (Burhans et al, 2015, Schreurs and Burhans, 2015).…”
Section: Introductionmentioning
confidence: 99%